Soil Chemical Properties and Nutrient Status on Various Land Slopes of Gayo Arabica Coffee Plantation, Aceh Indonesia - Muyassir Muyassir; Helmi Helmi; Meidilla Rahyunnisa (Aceh International Journal of Science and Technology, 2023)
The chemical and nutrient properties of soil on various land slopes are related to the management of integrated and sustainable coffee plantation. The aim of the study was to determine soil chemical properties and nutrient availability on various slopes of Gayo Arabica coffee plantations. A total of 12 composite soils for laboratory analysis were taken from Arabia coffee plantation owned by the community in Bandar District, Bener Meriah Regency. The selection of the research location was determined by purposive sampling. The independent variable was slope of the land, while dependent variables were soil chemical properties and available nutrients. The results showed that the soil chemical properties which were significantly different on various land slopes were C-organic, CN ratio, and base saturation. C-organic content and C:N ratio decreased with increasing slope of the Gayo Arabica coffee plantation. On the contrary, base saturation as the slope of the Gayo Arabica coffee fields rises.